The Role of Kyai in Pesantren Business Development: A Case Study on Leadership in The Traditional Pesantrens - Supriyanto Supriyanto Supriyanto; Zulfikar Zulfikar; Sukron Makmun; Salut Muhiddin (Program Studi Agribisnis, 2022)
The objective of this research is to explore the role of kyai leadership in developing pondok pesantren business unit to analyses the contribution of kyai in economy institution. This research is multisite case study in two pondok pesantren that are Sidogiri Pasuruan and Minhajut Thullab Banyuwangi. Analysis units of this research are kyai, teacher, ustadz, cooperative staffs, santri (student), society around pondok pesantren and pesantren cooperation members. The data were conducted by interview, observation, and document analysis. The design of this research is qualitative design applying multi sites case study technique model. Data analysis and data validity test using triangulation i.e source, method and time triangulation. The research shows that kyais have an important role in developing business unit of pesantren.